A review of factors impacting exposure to PM2.5, ultrafine particles and black carbon in Asian transport microenvironments. (August 2018) - Kumar, Prashant; Patton, Allison P.; Durant, John L.; Frey, H. Christopher
Abstract: The World Health Organization estimates 3.7 million deaths in 2012 in low- and middle-income Asian countries due to outdoor air pollution. However, these estimates do not account for the higher exposures of specific particulate matter (PM) components – including fine particles (PM2.5 ), ultrafine particles (UFP) and black carbon (BC) – typical of transport microenvironments (TMEs). With the rapidly growing number of on-road vehicles in Asia, human exposure to PM is an increasing concern. The aim of this review article is to comprehensively assess studies of PM2.5, UFP, and BC in Asian TMEs in order to better understand the extent of exposure, the underlying factors leading to exposure, and how Asian exposures compare to those found in Europe and the United States of America (USA). The health impacts of exposure to PM2.5, UFP, and BC are described and the key factors that influence personal exposure in TMEs (i.e., walk, cycle, car, and bus) are identified. Instrumentation and measurement methods, exposure modeling techniques, and regulation are reviewed for PM2.5, UFP, and BC. Relatively few studies have been carried out in urban Asian TMEs where PM2.5, UFP, and BC had generally higher concentrations compared to Europe and USA. Based on available data, PM2.5 concentrations while walking were 1.6 and 1.2 times higher in Asian cities (average 42 μg m −3 ) compared to cities in Europe (26 μg m −3 ) and the USA (35 μg m −3 ), respectively. Likewise, average PM2.5 concentrations in car (74 μg m −3 ) and bus (76 μg m −3 ) modes in Asian cities were approximately two to three times higher than in Europe and American cities. UFP exposures in Asian cities were twice as high for pedestrians and up to ∼9-times as high in cars than in cities in Europe or the USA. Asian pedestrians were exposed to ∼7-times higher BC concentrations compared with pedestrians in the USA. Stochastic population-based models have yet to be applied widely in Asia but can be used to quantify inter-individual and inter-regional variability in exposures and to assess the contribution of TMEs to total exposures for multiple pollutants. The review also highlights specific gaps in the Asian TME data set that need to be filled since UFP and BC studies were rare as were studies of pedestrian and cyclist exposure. Graphical abstract: Image 1 Highlights: PM, UFP and BC exposures are assessed for Asian transport microenvironments. Rare data on cyclist and motorcyclist exposure despite substantial use in Asian cities. Cyclists were relatively the least exposed while bus users showing highest exposure. Car users in Asia receive up to 9-times higher exposure to UFP to Europe and USA. Need more studies in diverse meteorological and traffic microenvironments in Asia.